Convocation - Osteen, Mark (Ars Medica, 2020)
This story recounts the author’s experiences with his adult autistic son during the latter’s hospitalization for a severe infection in 2018. Their re-entry into the “kingdom of illness” prompts the author to reconsider his beliefs about autism and intelligence, and to ponder the strange relationships that emerge in times of crisis. Inspired by one of those strange relations—between avian raptors and the American Super Bowl—the author interweaves facts about eagles (and The Eagles) into the essay. He finds that his son’s courage and strength redefine the concept of being a patient.